Columban simulation project: When pigeons replaced computers - Neves Filho, Hernando Borges (Perspectivas em Análise do Comportamento, 2018)
During the decade of 1980, Skinner and colleagues published a series of empirical research regarding themes such as symbolic communication, tool use, insight, self-awareness, and other popular themes of cognitive research. These papers were part of the so called Columban Simulation Project, an endeavor took by Skinner in his last years at Harvard, that aimed to recreate complex phenomena, easily observed in chimpanzees and humans, in pigeons. The project also had the objective to discuss the role of simulation research in Psychology experiments. The present essay offers a comprehensive description and discussion, in Portuguese, of all major papers related to the project. Implications of these papers to modern research in behavior analysis, cognitive science and computer science are discussed, among examples of some critics aimed to the project and also its lasting legacy to psychological research. It is concluded that the project had a reasonable impact in the scientific community at large, established a line of investigation of the operant determinants of problem solving performances, and that it also brought together discussions and data from research in behavior analysis, cognitive science and artificial intelligence.